Preparation method of composite polyurethane material for wear-resistant and impact-resistant sieve plate
Through the use of modified fluorosilicone resin and modified silicon filler, combined with the segment structure of low friction polyurethane, the problem of insufficient wear resistance and impact resistance of polyurethane screen material in high impact environments is solved, and the material is significantly improved Hardness and compatibility, a composite polyurethane screen with excellent performance was prepared.
Patent Information
- Application Number
- CN202411636549.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyurethane screen materials have insufficient wear resistance and impact resistance in high impact environments. Poor compatibility between materials leads to interface losses, affecting the purity and dimensional accuracy of the screen.
Using modified fluorosilicone resin and modified silicon filler, the surface energy and compatibility of the material are enhanced by hydrogen silicon addition and polytube reaction, combined with the segment structure of low friction polyurethane, and prepared by melt extrusion by twin screw extruder. Composite polyurethane material.
It significantly improves the hardness, wear resistance, tensile resistance and impact resistance of the material, reduces the friction coefficient, enhances compatibility with auxiliary materials, and prepares composite polyurethane materials with excellent wear resistance, smoothness, flame retardant and mechanical properties.
Smart Images

Figure CN119119410A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane processing, and in particular to a method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate. Background Art
[0002] After polyurethane material was introduced into screen plate manufacturing, it was favored due to its excellent wear resistance and impact resistance. In the initial stage, this material was mainly used for lighter screening tasks. With the development of chemical formula and processing technology, its wear resistance and tear strength have been significantly improved, adapting to more complex industrial applications; with the advancement of science and technology, the introduction of nanotechnology has further enhanced the structure of polyurethane and improved its performance in high impact environments.
[0003] Prior art CN108164981A discloses a polyurethane sieve plate and a preparation method thereof, which has high wear resistance, high strength, high hardness, light weight, high screening efficiency, no hole blocking, friction resistance, impact resistance, tear resistance, low noise, easy installation, long service life, large bearing capacity, and high comprehensive benefit. The polyurethane sieve plate and a preparation method thereof are composed of the following raw materials by weight: 100 parts of polyurethane prepolymer, 14-14.5 parts of MOCA, 5-8 parts of microsilica powder, 2-5 parts of zinc oxide and 1-2 parts of titanium dioxide; the raw materials selected by the invention are easy to obtain, the preparation process is simple to operate, and the prepared polyurethane sieve plate has strong wear resistance and good physical and chemical properties.
[0004] However, the above patent content is to mix the polyurethane prepolymer and auxiliary materials, and finally obtain the required polyurethane material through vulcanization. However, the polarity difference between the polyurethane prepolymer and the inorganic filler is large, which makes the interface bonding force between the materials weak, resulting in poor compatibility between the materials during the subsequent pouring process, affecting the structural stability of the screen plate, thereby forming interface loss during the screening process, resulting in reduced purity and dimensional accuracy of the screened material, and the auxiliary material composition is too single, with only vulcanizer and inorganic filler, so that the impact resistance and other properties of the polyurethane need to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a composite polyurethane material for wear-resistant and impact-resistant screen plates, so as to solve the technical problem in the prior art that the wear resistance and impact resistance of the composite polyurethane material for screen plates need to be further improved.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate comprises the following steps:
[0009] S1. Add polytetrahydrofuran, modified fluorosilicone resin, dibutyltin dilaurate and toluene into a reactor and stir. After the temperature of the reactor is raised to 60-80° C., add toluene-2,6-diisocyanate solution into the reactor and keep the temperature for 2-3 hours. After the reaction is completed, post-process to obtain low-friction polyurethane.
[0010] The reaction equation for preparing low friction polyurethane is:
[0011] Where: ; .
[0012] The reaction principle for preparing low-friction polyurethane is as follows: under the catalysis of a catalyst, a polymerization reaction occurs between the reactants and substrates to form a polyurethane structure with toluene-2,6-diisocyanate as the core of the chain segment, and finally a low-friction polyurethane is prepared.
[0013] S2, adding 80-100 parts of low-friction polyurethane, 20-30 parts of modified silicon filler, 10-15 parts of curing agent, 10-15 parts of thixotropic agent, 15-20 parts of plasticizer, 5-10 parts of flame retardant and 5-8 parts of antioxidant into a stirring tank and mixing evenly to obtain a mixture;
[0014] S3, adding the mixed material into a twin-screw extruder for melt extrusion to obtain a composite polyurethane.
[0015] Further, in step S1, the stirring rate of the reactor is 80-120rpm, the toluene-2,6-diisocyanate solution is prepared by mixing the toluene-2,6-diisocyanate solution and toluene in a dosage ratio of 1g:2mL, the dosage ratio of polytetrahydrofuran, modified fluorosilicone resin, dibutyltin dilaurate, toluene and toluene-2,6-diisocyanate solution is 4-5g:8-10g:0.2-0.5g:40-60mL:10-12mL, and the post-treatment includes: After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is produced to obtain a low-friction polyurethane; in step S2, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 180°C, 195, 195°C, 210°C, 210°C, 220°C, and 220°C, respectively, and the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar.
[0016] Furthermore, the curing agent is one or more of diphenylmethane diisocyanate, toluene diisocyanate and isophorone diisocyanate; the thixotropic agent is one or more of silicone thixotropic agent, calcium glycolate and expanded microspheres; the plasticizer is one or more of dioctyl phthalate, diisononyl phthalate and dibutyl phthalate; the flame retardant is one or two of melamine and hexabromocyclododecane; and the antioxidant is one or two of sulfided isobutylphenol and triphenyl phosphate.
[0017] Furthermore, the preparation method of the modified fluorosilicone resin comprises the following steps:
[0018] A1. Add hybrid silicone oil, molybdenum trichloride and toluene into a reactor and stir. After the temperature of the reactor is raised to 50-60° C., add tert-butyl peroxide into the reactor and stir for 1-2 hours. After the reaction is completed, post-process to obtain epoxy fluorosilicone resin.
[0019] The reaction equation for preparing epoxy fluorosilicone resin is:
[0020] The reaction principle for preparing epoxy fluorosilicone resin is as follows: under the catalytic oxidation of peroxide, the double bonds at the ends of the hybrid silicone oil segments are oxidized into epoxy groups, and finally epoxy fluorosilicone resin is prepared.
[0021] A2. Add epoxy fluorosilicone resin, triethylamine and toluene into a reactor. After the temperature of the reactor is raised to 40-60°C, add 2,3,4,5,6-pentafluorobenzoic acid into the reactor. Keep the temperature for 1-2 hours and perform post-treatment to obtain modified fluorosilicone resin.
[0022] The reaction equation for preparing modified fluorosilicone resin is:
[0023] Where: .
[0024] The reaction principle for preparing the modified fluorosilicone resin is as follows: under the catalysis of alkaline conditions, the epoxy groups on the epoxy fluorosilicone resin undergo a ring-opening reaction to generate free radicals that react with the carboxyl groups of 2,3,4,5,6-pentafluorobenzoic acid to finally prepare the modified fluorosilicone resin.
[0025] Furthermore, in step A1, the stirring rate of the reactor is 80-120rpm, the amount ratio of hybrid silicone oil, molybdenum trichloride, toluene and tert-butyl peroxide is 5-8g:0.2-0.5g:30-50mL:2-3g, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is filtered and the filtrate is collected, and the filtrate is added to a rotary evaporator with a water bath temperature of 80-100°C, and the epoxy fluorosilicone resin is distilled under reduced pressure until no liquid is produced, so as to obtain the epoxy fluorosilicone resin; in step A2, the amount ratio of epoxy fluorosilicone resin, triethylamine, toluene and 2,3,4,5,6-pentafluorobenzoic acid is 5-8g:0.2-0.5g:30-50mL:2-3g, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the vacuum distillation is performed until no liquid is produced to obtain a modified fluorosilicone resin.
[0026] Further, the preparation method of the hybrid silicone oil is:
[0027] B1, trifluoropropylmethylcyclotrisiloxane, tetrafluoromethoxythrin, bis(dimethyl(vinyl)silyl)platinum dihydride and toluene are added to a reaction kettle, the temperature of the reaction kettle is increased to 30-40° C., the reaction is kept warm for 1-2 hours, and post-processed to obtain modified cyclosilane;
[0028] The reaction equation for preparing modified cyclosilane is:
[0029] Where: ; .
[0030] The reaction principle for preparing modified cyclosilane is: under the initiation of the catalyst, the silicon-hydrogen bond on trifluoropropylmethylcyclotrisiloxane and the double bond on tetrafluoromethyl ether thiram undergo silylation reaction to finally prepare the modified cyclosilane. The mass spectrometry analysis data of the modified cyclosilane are m / z: 1590.52 (100.0%), 1591.52 (91.3%), 1592.52 (42.6%), 1593.52 (14.7%), 1592.51 (10.1%), 1593.53 (7.2%), 1594.52 (4.4%), 1594.53 (3.1%), 1595.52 (1.2%), 1593.51 (1.0%).
[0031] B2, adding modified cyclosilane, tetramethyldivinyldisiloxane, methyl silicone oil and diethyl ether into a reaction kettle, stirring at room temperature for 15-20 minutes to obtain a reaction precursor solution;
[0032] B3. Add the reaction precursor solution and 98wt% sulfuric acid solution into the reactor, keep the reaction at room temperature for 8-10h, add solid sodium bicarbonate into the reactor containing the reaction solution until the pH value of the reaction solution is 7-8, and then perform post-treatment to obtain hybrid silicone oil.
[0033] The reaction equation for preparing hybrid silicone oil is:
[0034] The reaction principle for preparing hybrid silicone oil is as follows: under the catalytic action of concentrated sulfuric acid, the reactant substrate is hydrolyzed, tetramethyldivinyldisiloxane is used as a telogen, modified cyclosilane and methyl silicone oil are used as main chain monomer substances, and at the same time, the carbon-oxygen-silicon structure of the side chain is hydrolyzed, and finally the hybrid silicone oil is prepared.
[0035] Further, in step B1, the amount ratio of trifluoropropylmethylcyclotrisiloxane, tetrafluoromethoxythrin, bis(dimethyl(vinyl)silyl)dihydrogenplatinum and toluene is 8-10g:3-5g:0.2-0.5g:40-60mL, the stirring rate of the reactor is 40-60rpm, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction solution is distilled under reduced pressure until no liquid is extracted to obtain a modified cyclosilane; in step B2, the reaction is The stirring rate of the kettle is 80-120rpm, and the amount ratio of modified cyclosilane, tetramethyldivinyldisiloxane, methyl silicone oil and ether is 5-6g:2-3g:4-5g:40-60mL; in step B3, the amount ratio of the reaction precursor solution and the 98wt% sulfuric acid solution is 20-30mL:4-5mL, and the post-treatment includes: after the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the hybrid silicone oil is obtained by reduced pressure distillation until no liquid is produced.
[0036] Furthermore, the preparation method of the modified silicon filler comprises the following steps:
[0037] C1. Add triethoxysilane and ethanol into a reactor and stir. After the temperature of the reactor rises to 50-60° C., add 5-10 wt % ammonia solution into the reactor, control the pH of the solution to 9-11, keep warm and stir for 6-8 hours. After the reaction is completed, post-treat to obtain modified nano-silicon dioxide particles;
[0038] C2. Add nano-silicon dioxide particles and dimethyl sulfoxide into a reactor. After the temperature of the reactor is raised to 60-80°C, add the polymer solution into the reactor and keep the temperature for 4-6 hours. After the reaction is completed, post-process to obtain modified silicon filler.
[0039] Reaction principle: Under alkaline conditions, triethoxysilane is hydrolyzed to produce silanol groups, which undergo condensation to further form a spatial network structure. After the reaction is completed, modified nano-silica particles are obtained through high-temperature calcination and oxidation. The active groups on the surface of the particles attract the reactive monomers to polymerize in situ on their surface, eventually forming a coating structure to obtain a modified silicon filler.
[0040] Further, in step C1, the stirring rate of the reactor is 80-120rpm, the amount ratio of triethoxysilane and ethanol is 10-15mL:40-60mL, and the post-treatment includes: after the temperature of the reactor is reduced to room temperature, the reactor is transferred to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced, and the bottom precipitate is collected. The precipitate is transferred to a tubular furnace, and after nitrogen protection is introduced, the tubular furnace is heated to 400-600°C at a heating rate of 5°C / min. After heat preservation for 2-3h, oxygen is introduced into the tubular furnace at a rate of 0.5-1.5L. / min, heat preservation for 1-2h, to obtain nano silicon dioxide particles; in step C2, the amount ratio of nano silicon dioxide particles, dimethyl sulfoxide and polymer solution is 8-10g:30-40mL:10-20mL, the polymer solution is prepared by 3-(methacryloyloxy)propyltrimethoxysilane, azobisisobutyronitrile and dimethyl sulfoxide in an amount ratio of 5-8g:2-3g:15-20mL, and the post-treatment includes: after the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain a modified silicon filler.
[0041] The present invention has the following beneficial effects:
[0042] 1. In the composite polyurethane prepared by the present invention, the chain segment structure inside the component composite polyurethane has a large number of fluorine groups and siloxy groups, wherein a large number of fluorine groups make the composite polyurethane have extremely strong surface energy, and significantly reduce the friction coefficient of the material. As the material of the sieve plate, it reduces the screening efficiency and reduces the material wear. A large number of siloxane groups enhance its compatibility with the modified silicon filler prepared by the present invention, and the two cooperate to achieve the effect of resistance reduction and flame retardancy. The polymer formed on the surface of the modified silicon filler after in-situ assembly has a large number of silane coupling agent structures, which serve as a bridge to make the low-friction polyurethane material with high surface energy have excellent compatibility with the auxiliary materials, further enhance the hardness and wear resistance, tensile strength and impact resistance of the material, and finally prepare a wear-resistant, smooth, flame-retardant and mechanically excellent composite polyurethane.
[0043] 2. In the process of preparing a low-friction polyurethane according to the present invention, the surface of trifluoropropylmethylcyclotrisiloxane is firstly modified, and fluorine groups are further introduced on its surface by hydrosilylation, and a hybrid silicone oil is obtained by polyol polymerization, and the end thereof is further modified to obtain a modified fluorosilicone resin, which serves as one of the chain segments of the low-friction polyurethane. A large number of fluorine groups on its surface significantly enhance the surface energy of the material and reduce the friction coefficient. A large number of silane structures significantly improve the flame retardancy and wear resistance of the material, and enhance the polarity of the material, thereby significantly improving its compatibility with inorganic auxiliary materials.
[0044] 3. In the process of preparing modified silicon filler, the present invention first prepares a modified nano-silica particle by hydrolysis, and forms a polymer structure on its surface by in-situ assembly. While enhancing its stability, the silane coupling agent structure on the polymer surface makes it excellently compatible with the polyurethane component and auxiliary materials containing the siloxane structure, so that the components are tightly combined, and the wear resistance, impact resistance and tensile resistance of the material are significantly improved. The organic polymer structure attached to its surface can significantly reduce its polarity, so that its compatibility with organic materials is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 This is a SEM image of the modified silicon filler prepared in the present invention. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The polytetrahydrofuran used in the present invention was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., with the product number MKL-P903557; the hydroxy silicone oil used in the present invention was purchased from Shandong Longhui Chemical Co., Ltd.;
[0049] Example 1
[0050] This embodiment provides a method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate, comprising the following steps:
[0051] S1. Preparation of hybrid silicone oil
[0052] Weigh: 16.0 g of trifluoropropylmethylcyclotrisiloxane, 8.0 g of tetrafluoromethoxythrin, 0.4 g of bis(dimethyl(vinyl)silyl)dihydrogenplatinum and 100.0 mL of toluene, add them into a reactor, raise the temperature of the reactor to 30° C., keep the temperature for 1 hour, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80° C., and distill under reduced pressure until no liquid is produced to obtain a modified cyclosilane;
[0053] Weigh: 10.0 g of modified cyclosilane, 5.0 g of tetramethyldivinyldisiloxane, 8.0 g of methyl silicone oil and 100.0 mL of ether, add into a reaction kettle, stir at room temperature for 15 min, stirring at a rate of 80 rpm, to obtain a reaction precursor solution;
[0054] Weigh: 40.0 mL of reaction precursor solution and 9.0 mL of 98 wt% sulfuric acid solution are added to the reactor. After the reaction is kept warm for 8 hours at room temperature, solid sodium bicarbonate is added to the reactor containing the reaction solution until the pH of the reaction solution is 7. After the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain hybrid silicone oil.
[0055] S2. Preparation of low friction polyurethane
[0056] Weigh: 12.0g hybrid silicone oil, 0.6g molybdenum trichloride and 80.0mL toluene, add to the reactor and stir at a stirring rate of 80rpm. After the temperature of the reactor is raised to 50°C, add 5.0g tert-butyl peroxide to the reactor, keep warm and stir for 1h. After the reaction is completed, the reactor is lowered to room temperature, the reaction liquid is filtered and the filtrate is collected. The filtrate is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain epoxy fluorosilicone resin;
[0057] Weigh: 12.0 g of epoxy fluorosilicone resin, 0.8 g of triethylamine and 80.0 mL of toluene are added to a reactor. After the temperature of the reactor is raised to 40° C., 5.0 g of 2,3,4,5,6-pentafluorobenzoic acid is added to the reactor and the reaction is carried out for 1 hour. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid is produced to obtain a modified fluorosilicone resin;
[0058] Weigh: 20.0 g of toluene-2,6-diisocyanate solution and 40.0 mL of toluene to obtain a toluene-2,6-diisocyanate solution;
[0059] Weigh: 12.0g of polytetrahydrofuran, 27.0g of modified fluorosilicone resin, 1.0g of dibutyltin dilaurate and 120.0mL of toluene, add into the reactor and stir at a stirring rate of 80rpm. After the temperature of the reactor is raised to 60°C, add 32.0mL of toluene-2,6-diisocyanate solution into the reactor and keep warm for 2h. After the reaction is completed, wait for the reactor to cool to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain a low friction polyurethane.
[0060] S3. Preparation of modified silicon filler
[0061] Weigh: 20.0mL triethoxysilane and 80.0mL ethanol are added to a reactor and stirred at a stirring rate of 80rpm. After the temperature of the reactor rises to 50°C, 8.0wt% ammonia solution is added dropwise to the reactor, the pH of the solution is controlled to 9, and the reaction is stirred for 6h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reactor is transferred to a rotary evaporator with a water bath temperature of 80°C, and vacuum distillation is performed until no liquid is produced. The bottom precipitate is collected and transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 400°C at a heating rate of 5°C / min. After heat treatment for 2h, oxygen is introduced into the tubular furnace at a rate of 0.5L / min. The heat treatment is performed for 1h to obtain nano-silicon dioxide particles;
[0062] Weigh: 12.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 5.0 g of azobisisobutyronitrile and 30.0 mL of dimethyl sulfoxide to prepare a polymer solution;
[0063] Weigh: 18.0g of nano-silicon dioxide particles and 6.0g of dimethyl sulfoxide are added to the reactor. After the temperature of the reactor is raised to 60°C, 45.0mL of the polymer solution is added to the reactor and the reaction is kept warm for 4h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at 80°C and vacuum dried until the filter cake has a constant weight to obtain a modified silicon filler.
[0064] S4. Preparation of composite polyurethane
[0065] Weigh: 84.0 g of low-friction polyurethane, 24.0 g of modified silicon filler, 12.0 g of diphenylmethane diisocyanate, 12.0 g of calcium glycolate, 16.0 g of dioctyl phthalate, 8.0 g of hexabromocyclododecane and 6.4 g of triphenyl phosphate, add into a stirring tank and mix well to obtain a mixture;
[0066] The mixed material is added into a twin-screw extruder, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port are 180°C, 195, 195°C, 210°C, 210°C, 220°C, and 220°C respectively, the main engine speed of the twin-screw extruder is 80rpm, and the pressure is 100bar, and the composite polyurethane is obtained by melt extrusion.
[0067] Example 2
[0068] This embodiment provides a method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate, comprising the following steps:
[0069] S1. Preparation of hybrid silicone oil
[0070] Weigh: 18.0 g of trifluoropropylmethylcyclotrisiloxane, 8.0 g of tetrafluoromethoxythrin, 0.8 g of bis(dimethyl(vinyl)silyl)dihydrogenplatinum and 100.0 mL of toluene, add them into a reactor, raise the temperature of the reactor to 40° C., keep the temperature for 2 h, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100° C., and distill under reduced pressure until no liquid is produced to obtain a modified cyclosilane;
[0071] Weigh: 10.0 g of modified cyclosilane, 5.0 g of tetramethyldivinyldisiloxane, 8.0 g of methyl silicone oil and 100.0 mL of ether, add into a reaction kettle, stir at room temperature for 20 min at a stirring rate of 120 rpm, and obtain a reaction precursor solution;
[0072] Weigh: 50.0 mL of reaction precursor solution and 9.0 mL of 98 wt% sulfuric acid solution are added to the reactor. After the reaction is kept warm for 10 hours at room temperature, solid sodium bicarbonate is added to the reactor containing the reaction solution until the pH of the reaction solution is 8. After the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain hybrid silicone oil.
[0073] S2. Preparation of low friction polyurethane
[0074] Weigh: 18.0g hybrid silicone oil, 1.0g molybdenum trichloride and 100.0mL toluene are added to the reactor and stirred at a stirring rate of 80rpm. After the temperature of the reactor is raised to 60°C, 7.2g tert-butyl peroxide is added to the reactor and stirred for 2h. After the reaction is completed, the reactor is lowered to room temperature, the reaction liquid is filtered and the filtrate is collected. The filtrate is added to a rotary evaporator with a water bath temperature of 80°C, and the epoxy fluorosilicone resin is obtained by reduced pressure distillation until no liquid is produced;
[0075] Weigh: 18.0 g of epoxy fluorosilicone resin, 0.8 g of triethylamine and 100.0 mL of toluene are added to a reactor. After the temperature of the reactor is raised to 60° C., 7.2 g of 2,3,4,5,6-pentafluorobenzoic acid is added to the reactor. The reaction is kept warm for 2 hours. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100° C., and distilled under reduced pressure until no liquid is produced to obtain a modified fluorosilicone resin;
[0076] Weigh: 20.0 g of toluene-2,6-diisocyanate solution and 40.0 mL of toluene to obtain a toluene-2,6-diisocyanate solution;
[0077] Weigh: 12.0g of polytetrahydrofuran, 24.0g of modified fluorosilicone resin, 1.2g of dibutyltin dilaurate and 120.0mL of toluene, add into the reactor and stir at a stirring rate of 120rpm. After the temperature of the reactor is raised to 80°C, add 30.0mL of toluene-2,6-diisocyanate solution into the reactor and keep warm for 3h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added into a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain a low friction polyurethane.
[0078] S3. Preparation of modified silicon filler
[0079] Weigh: 24.0mL triethoxysilane and 120.0mL ethanol are added to a reactor and stirred at a stirring rate of 120rpm. After the temperature of the reactor rises to 60°C, 8.0wt% ammonia solution is added dropwise to the reactor, the pH of the solution is controlled to 11, and the reaction is stirred for 8h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reactor is transferred to a rotary evaporator with a water bath temperature of 100°C, and vacuum distillation is performed until no liquid is produced. The bottom precipitate is collected and transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 600°C at a heating rate of 5°C / min. After heat treatment for 3h, oxygen is introduced into the tubular furnace at a rate of 1.5L / min. The heat treatment is performed for 2h to obtain nano-silicon dioxide particles.
[0080] Weigh: 16.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 6.0 g of azobisisobutyronitrile and 32.0 mL of dimethyl sulfoxide to prepare a polymer solution;
[0081] Weigh: 12.0g of nano-silicon dioxide particles and 5.0g of dimethyl sulfoxide are added to the reactor. After the temperature of the reactor is raised to 80°C, 32.0mL of the polymer solution is added to the reactor and the reaction is kept warm for 6 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain a modified silicon filler.
[0082] S4. Preparation of composite polyurethane
[0083] Weigh: 90.0 g of low-friction polyurethane, 20.0 g of modified silicon filler, 12.0 g of diphenylmethane diisocyanate, 13.2 g of calcium glycolate, 16.0 g of dioctyl phthalate, 8.0 g of hexabromocyclododecane and 7.2 g of triphenyl phosphate, add into a stirring tank and mix well to obtain a mixture;
[0084] The mixed material is added into a twin-screw extruder, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port are 180°C, 195, 195°C, 210°C, 210°C, 220°C, 220°C, the main engine speed of the twin-screw extruder is 120rpm, and the pressure is 150bar, and the composite polyurethane is obtained by melt extrusion.
[0085] Example 3
[0086] This embodiment provides a method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate, comprising the following steps:
[0087] S1. Preparation of hybrid silicone oil
[0088] Weigh: 18.0 g of trifluoropropylmethylcyclotrisiloxane, 10.0 g of tetrafluoromethoxythrin, 0.8 g of bis(dimethyl(vinyl)silyl)platinum dihydride and 120.0 mL of toluene, add them into a reactor, raise the temperature of the reactor to 35° C., keep the temperature for 2 h, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 90° C., and distill under reduced pressure until no liquid is produced to obtain a modified cyclosilane;
[0089] Weigh: 12.0 g of modified cyclosilane, 5.0 g of tetramethyldivinyldisiloxane, 9.0 g of methyl silicone oil and 100.0 mL of ether, add into a reaction kettle, stir at room temperature for 18 min, and stir at a rate of 100 rpm to obtain a reaction precursor solution;
[0090] Weigh: 40.0 mL of reaction precursor solution and 10.0 mL of 98 wt% sulfuric acid solution are added to the reactor. After the reaction is kept warm for 9 hours at room temperature, solid sodium bicarbonate is added to the reactor containing the reaction solution until the pH of the reaction solution reaches 8. After the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain hybrid silicone oil.
[0091] S2. Preparation of low friction polyurethane
[0092] Weigh: 16.0g hybrid silicone oil, 0.8g molybdenum trichloride and 80.0mL toluene are added to the reactor and stirred at a stirring rate of 100rpm. After the temperature of the reactor is raised to 55°C, 6.0g tert-butyl peroxide is added to the reactor, and the mixture is stirred for 2h. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is filtered, and the filtrate is collected. The filtrate is added to a rotary evaporator with a water bath temperature of 100°C, and the epoxy fluorosilicone resin is obtained by vacuum distillation until no liquid is produced;
[0093] Weigh: 16.0g of epoxy fluorosilicone resin, 1.0g of triethylamine and 80.0mL of toluene are added to a reactor. After the temperature of the reactor is raised to 100°C, 5.0g of 2,3,4,5,6-pentafluorobenzoic acid is added to the reactor and the reaction is carried out for 2h. After the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain a modified fluorosilicone resin;
[0094] Weigh: 20.0 g of toluene-2,6-diisocyanate solution and 40.0 mL of toluene to obtain a toluene-2,6-diisocyanate solution;
[0095] Weigh: 10.0g of polytetrahydrofuran, 16.0g of modified fluorosilicone resin, 0.8g of dibutyltin dilaurate and 80.0mL of toluene, add into the reactor and stir at a stirring rate of 100rpm. After the temperature of the reactor is raised to 70°C, add 24.0mL of toluene-2,6-diisocyanate solution into the reactor and keep warm for 3h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added into a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain a low friction polyurethane.
[0096] S3. Preparation of modified silicon filler
[0097] Weigh: 30.0mL triethoxysilane and 80.0mL ethanol are added to a reactor and stirred at a stirring rate of 100rpm. After the temperature of the reactor rises to 50°C, 8.0wt% ammonia solution is added dropwise to the reactor, the pH of the solution is controlled to 10, and the reaction is stirred for 7h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reactor is transferred to a rotary evaporator with a water bath temperature of 80°C, and vacuum distillation is performed until no liquid is produced. The bottom precipitate is collected and transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 500°C at a heating rate of 5°C / min. After heat treatment for 3h, oxygen is introduced into the tubular furnace at a rate of 1.0L / min, and the heat treatment is performed for 2h to obtain nano-silicon dioxide particles;
[0098] Weigh: 12.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 6.0 g of azobisisobutyronitrile and 30.0 mL of dimethyl sulfoxide to prepare a polymer solution;
[0099] Weigh: 12.0g of nano-silicon dioxide particles and 6.0g of dimethyl sulfoxide are added to the reactor. After the temperature of the reactor is raised to 70°C, 30.0mL of the polymer solution is added to the reactor and the reaction is kept warm for 5h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at 80°C and vacuum dried until the filter cake has a constant weight to obtain a modified silicon filler.
[0100] S4. Preparation of composite polyurethane
[0101] Weigh: 96.0 g of low-friction polyurethane, 24.0 g of modified silicon filler, 12.0 g of diphenylmethane diisocyanate, 12.0 g of calcium glycolate, 16.0 g of dioctyl phthalate, 8.4 g of hexabromocyclododecane and 7.2 g of triphenyl phosphate, add into a stirring tank and mix well to obtain a mixture;
[0102] The mixed material is added into a twin-screw extruder, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port are 180°C, 195, 195°C, 210°C, 210°C, 220°C, and 220°C, respectively, the main engine speed of the twin-screw extruder is 100 rpm, and the pressure is 125 bar, and the composite polyurethane is obtained by melt extrusion.
[0103] Comparative Example 1
[0104] The difference between this comparative example and Example 3 is that step S1 is eliminated, and in step S2, an equal amount of hydroxy silicone oil is used to replace the hybrid silicone oil.
[0105] Comparative Example 2
[0106] The difference between this comparative example and Example 3 is that step S1 and step S2 are eliminated, and in step S4, an equal amount of polyurethane is used to replace the low-friction polyurethane.
[0107] Comparative Example 3
[0108] The difference between this comparative example and Example 3 is that step S1 and step S2 are eliminated, and in step S4, an equal amount of polyurethane is used to replace the low-friction polyurethane.
[0109] Comparative Example 3
[0110] The difference between this comparative example and Example 3 is that step S1 and step S2 are eliminated, and in step S4, an equal amount of polyurethane is used to replace the low-friction polyurethane.
[0111] Performance Test:
[0112] The relative volume wear, hardness and tensile strength of the composite polyurethanes prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 33091-2016 "Polyurethane Sieve Plate";
[0113] The Izod impact strength of the composite polyurethanes prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 1843-2008 "Determination of Izod impact strength of plastics";
[0114] The friction coefficients of the composite polyurethanes prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 40721-2021 “Determination of friction properties of rubber”;
[0115] The limiting oxygen index of the composite polyurethanes prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 26526-2011 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test";
[0116] The specific results are shown in Table 1.
[0117] Table 1-Performance test data of each sample
[0118] Data Analysis:
[0119] Comparing and analyzing the data in Table 1 above, the relative volume wear of the composite polyurethane prepared by the present invention is 46 mm 3 , hardness is 86A, tensile strength is 51MPa, cantilever beam impact strength is 67.2kJ·m -2 , the friction coefficient is 0.072 and the limiting oxygen index is 39.5%, indicating that:
[0120] The invention prepares a hybrid silicone oil having a large number of fluorine groups in the side chain through a polycondensation reaction, and obtains fluorosilicone rubber after modifying the end of the chain segment. The fluorosilicone rubber is one of the main chain segments of low-friction polyurethane. The large number of fluorine groups inside the fluorosilicone rubber makes the low-friction polyurethane have extremely high surface energy, thereby reducing its friction coefficient and making the passability of the sieve plate excellent. The large number of siloxy groups inside the fluorosilicone rubber enhance the wear resistance and flame retardancy of the low-friction polyurethane and make it have excellent compatibility with the modified silicon filler prepared by the invention. The polymer obtained by in-situ assembly on the surface of the modified silicon filler contains a large number of silane coupling agent structures, which significantly enhances the polymerization ability between materials, so that the final product composite polyurethane has excellent hardness, tensile strength, wear resistance and impact resistance, and finally prepares a composite polyurethane with wear resistance, smoothness, flame retardancy and excellent mechanical properties.
[0121] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0122] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0123] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate, It is characterized in that The following steps are involved: S1. Add polytetrahydrofuran, modified fluorosilicone resin, dibutyltin dilaurate and toluene into a reactor and stir. After the temperature of the reactor is raised to 60-80° C., add toluene-2,6-diisocyanate solution into the reactor and keep the temperature for 2-3 hours. After the reaction is completed, post-process to obtain low-friction polyurethane. S2, adding 80-100 parts of low-friction polyurethane, 20-30 parts of modified silicon filler, 10-15 parts of curing agent, 10-15 parts of thixotropic agent, 15-20 parts of plasticizer, 5-10 parts of flame retardant and 5-8 parts of antioxidant into a stirring tank and mixing evenly to obtain a mixture; S3, adding the mixed material into a twin-screw extruder for melt extrusion to obtain a composite polyurethane.
2. A method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate according to claim 1, It is characterized in that In step S1, the stirring rate of the reactor is 80-120rpm, the toluene-2,6-diisocyanate solution is prepared by mixing the toluene-2,6-diisocyanate solution and toluene in a dosage ratio of 1g:2mL, and the dosage ratio of polytetrahydrofuran, modified fluorosilicone resin, dibutyltin dilaurate, toluene and toluene-2,6-diisocyanate solution is 4-5g:8-10g:0.2-0.5g:40-60mL:10-12mL.
3. The method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate according to claim 1, It is characterized in that The preparation method of the modified fluorosilicone resin comprises the following steps: A1. Add hybrid silicone oil, molybdenum trichloride and toluene into a reactor and stir. After the temperature of the reactor is raised to 50-60° C., add tert-butyl peroxide into the reactor and stir for 1-2 hours. After the reaction is completed, post-process to obtain epoxy fluorosilicone resin. A2. Add epoxy fluorosilicone resin, triethylamine and toluene into a reactor. After the temperature of the reactor is raised to 40-60°C, add 2,3,4,5,6-pentafluorobenzoic acid into the reactor. Keep the temperature for 1-2 hours and perform post-treatment to obtain modified fluorosilicone resin.
4. The method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate according to claim 3, It is characterized in that In step A1, the stirring rate of the reactor is 80-120rpm, and the amount ratio of hybrid silicone oil, molybdenum trichloride, toluene and tert-butyl peroxide is 5-8g:0.2-0.5g:30-50mL:2-3g; in step A2, the amount ratio of epoxy fluorosilicone resin, triethylamine, toluene and 2,3,4,5,6-pentafluorobenzoic acid is 5-8g:0.2-0.5g:30-50mL:2-3g.
5. The method for preparing a composite polyurethane material for wear-resistant and impact-resistant screen plates according to claim 3, It is characterized in that The preparation method of the hybrid silicone oil is: B1, trifluoropropylmethylcyclotrisiloxane, tetrafluoromethoxythrin, bis(dimethyl(vinyl)silyl)platinum dihydride and toluene are added to a reaction kettle, the temperature of the reaction kettle is increased to 30-40° C., the reaction is kept warm for 1-2 hours, and post-processed to obtain modified cyclosilane; B2, adding modified cyclosilane, tetramethyldivinyldisiloxane, methyl silicone oil and diethyl ether into a reaction kettle, stirring at room temperature for 15-20 minutes to obtain a reaction precursor solution; B3. Add the reaction precursor solution and 98wt% sulfuric acid solution into the reactor, keep the reaction at room temperature for 8-10h, add solid sodium bicarbonate into the reactor containing the reaction solution until the pH value of the reaction solution is 7-8, and then perform post-treatment to obtain hybrid silicone oil.
6. The method for preparing a composite polyurethane material for wear-resistant and impact-resistant screen plates according to claim 5, It is characterized in that In step B1, the amount ratio of trifluoropropylmethylcyclotrisiloxane, tetrafluoromethoxythrin, bis(dimethyl(vinyl)silyl)dihydrogenplatinum and toluene is 8-10g:3-5g:0.2-0.5g:40-60mL, and the stirring rate of the reactor is 40-60rpm; in step B2, the amount ratio of modified cyclosilane, tetramethyldivinyldisiloxane, methyl silicone oil and ether is 5-6g:2-3g:4-5g:40-60mL; in step B3, the amount ratio of the reaction precursor solution and 98wt% sulfuric acid solution is 20-30mL:4-5mL.
7. The method for preparing a composite polyurethane material for a wear-resistant and impact-resistant screen plate according to claim 1, It is characterized in that The preparation method of the modified silicon filler comprises the following steps: C1. Add triethoxysilane and ethanol into a reactor and stir. After the temperature of the reactor rises to 50-60° C., add 5-10 wt % ammonia solution into the reactor, control the pH of the solution to 9-11, keep warm and stir for 6-8 hours. After the reaction is completed, post-treat to obtain modified nano-silicon dioxide particles; C2. Add nano-silicon dioxide particles and dimethyl sulfoxide into a reactor. After the temperature of the reactor is raised to 60-80°C, add the polymer solution into the reactor and keep the temperature for 4-6 hours. After the reaction is completed, post-process to obtain modified silicon filler.
8. The method for preparing a composite polyurethane material for wear-resistant and impact-resistant screen plates according to claim 7, It is characterized in that In step C1, the stirring rate of the reaction kettle is 80-120rpm, and the dosage ratio of triethoxysilane to ethanol is 10-15mL:40-60mL; in step C2, the dosage ratio of nano-silica particles, dimethyl sulfoxide and polymer solution is 8-10g:30-40mL:10-20mL, and the polymer solution is prepared by preparing 3-(methacryloyloxy)propyltrimethoxysilane, azobisisobutyronitrile and dimethyl sulfoxide in a dosage ratio of 5-8g:2-3g:15-20mL.
Citation Information
Patent Citations
Impact-resistant polyurethane sieve plate for sieving ore
CN110760178A
Polyurethane material and preparation method thereof
CN112898518A
Polyurethane acrylate hybrid fluorine-containing silicon resin, preparation method and application
CN114106282A
High-strength wear-resistant polyurethane composite board and processing technology thereof
CN116872592A
Polyurethane elastomer, modified silicone rubber, acoustic lens, and ultrasonic probe
CN117164804A
Cited By
Preparation method and application of color master batch
CN119639203A
